Recommendations for the use of andexanet alfa in the management of bleeding in patients on oral factor Xa inhibitors in Switzerland - Anne Angelillo-Scherrer; Alessandro Casini; Jan-Dirk Studt; Bernhard Gerber; Lorenzo A. Alberio; Pierre Fontana (Swiss Medical Weekly, 2023)
Anticoagulants are essential in preventing and treating thrombosis. Unfortunately, their use is accompanied by an enhanced risk of bleeding. Since the introduction of direct oral anticoagulants (DOACs), the risk of major bleeding has been reduced but not eliminated. Major bleeding events related to the use of factor Xa inhibitors can be challenging to manage. In recent years, four-factor prothrombin complex concentrates have been used in patients with severe bleeding taking oral direct factor Xa inhibitors (apixaban, edoxaban and rivaroxaban). Andexanet alfa (OndexxyaTM, AstraZeneca AG) is a specially designed recombinant version of human factor Xa that acts as a decoy receptor to reverse the effects of factor Xa inhibitors. Since 2 December 2020, andexanet alfa has been used in Switzerland for adult patients receiving apixaban or rivaroxaban when reversal of anticoagulation is required because of life-threatening or uncontrolled bleeding. However, the use of andexanet alfa remains a challenge owing to its cost, the reported thrombotic complications and the fact that its efficacy mainly relates to intracranial haemorrhage. Moreover, the use of nonspecific reversal agents together with andexanet alfa is controversial. The present recommendations on the use of andexanet alfa in the management of bleeding in patients on factor Xa inhibitors in Switzerland were developed by a group of Swiss experts from the Working Party Hemostasis of the Swiss Society of Hematology. These recommendations aim to provide support to clinicians in their decision-making in the management of patients with major bleeding receiving factor Xa inhibitors.